Evaluasi Pengembangan Karir dalam Meningkatkan Profesionalisme Guru di SDN Pakis 1/368 - Wulan Ndari, Novita; Illa Azzahra, Naya; Rafifatur Rozany, Nasywa; Trihantoyo, Syunu; Nuphanudin, Nuphanudin (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2024)
Teacher career development is an important aspect in improving professionalism and the quality of education in elementary schools. This study aims to evaluate the effectiveness of the career development program in increasing teacher professionalism at SDN Pakis 1/368. This research uses a qualitative research method with a case study approach. Through observations, interviews and analysis of documents related to career development programs and teacher professionalism, the research results show that the career development program at SDN Pakis 1/368 has had a positive impact in increasing teacher professionalism. Teachers who participated in the program demonstrated improvements in understanding of current educational concepts, teaching skills, and motivation to improve their performance. In addition, participation in career development activities also increases collaboration between teachers and strengthens a culture of continuous learning in schools. The practical implications of these findings can help policy makers and educational practitioners in designing and implementing effective career development programs to improve the quality of education at the educational level. base.